Identification of Nitrogen-Fixing Bradyrhizobium Associated With Roots of Field-Grown Sorghum by Metagenome and Proteome Analyses - Hara, Shintaro; Morikawa, Takashi; Wasai, Sawa; Kasahara, Yasuhiro; Koshiba, Taichi; Yamazaki, Kiyoshi; Fujiwara, Toru; Tokunaga, Tsuyoshi; Minamisawa, Kiwamu (Frontiers in Microbiology, 2019)
Sorghum (Sorghum bicolor) is cultivated worldwide for food, bioethanol, and fodder production. Although nitrogen fixation in sorghum has been studied since the 1970s, N2-fixing bacteria have not been widely examined in field-grown sorghum plants because the identification of functional diazotrophs depends on the culture method used. The aim of this study was to identify functional N2-fixing bacteria associated with field-grown sorghum by using “omics” approaches. Four lines of sorghum (KM1, KM2, KM4, and KM5) were grown in a field in Fukushima, Japan. The nitrogen-fixing activities of the roots, leaves, and stems were evaluated by acetylene reduction and 15N2-feeding assays. The highest nitrogen-fixing activities were detected in the roots of lines KM1 and KM2 at the late growth stage. Bacterial cells extracted from KM1 and KM2 roots were analyzed by metagenome, proteome, and isolation approaches and their DNA was isolated and sequenced. Nitrogenase structural gene sequences in the metagenome sequences were retrieved using two nitrogenase databases. Most sequences were assigned to nifHDK of Bradyrhizobium species, including non-nodulating Bradyrhizobium sp. S23321 and photosynthetic B. oligotrophicum S58T. Amplicon sequence and metagenome analysis revealed a relatively higher abundance (2.9–3.6%) of Bradyrhizobium in the roots. Proteome analysis indicated that three NifHDK proteins of Bradyrhizobium species were consistently detected across sample replicates. By using oligotrophic media, we purified eight bradyrhizobial isolates. Among them, two bradyrhizobial isolates possessed 16S rRNA and nif genes similar to those in S23321 and S58T which were predicted as functional diazotrophs by omics approaches. Both free-living cells of the isolates expressed N2-fixing activity in a semi-solid medium according to an acetylene reduction assay. These results suggest that major functional N2-fixing bacteria in sorghum roots are unique bradyrhizobia that resemble photosynthetic B. oligotrophicum S58T and non-nodulating Bradyrhizobium sp. S23321. Based on our findings, we discuss the N2-fixing activity level of sorghum plants, phylogenetic and genomic comparison with diazotrophic bacteria in other crops, and Bradyrhizobium diversity in N2 fixation and nodulation.